The influence of V microalloying on the hot deformation behavior and microstructure evolution of high-manganese steel for LNG storage tanks - Yu-chen Li; Ji-guang Li; Da-zheng Zhang; Qi-hang Pang (Journal of Materials Research and Technology)
Herein, the high-temperature hot deformation and dynamic recrystallization (DRX) behavior of high-manganese steel were investigated through the measurement of true stress-strain curves, the establishment of constitutive equations, the construction of recrystallization and hot processing maps, and the characterization of microstructure evolution. Furthermore, the influence of V on the DRX behavior of high-manganese steel during the hot deformation process, particularly for LNG storage tanks, was systematically evaluated. The results indicate that both the critical stress (σc) and peak stress (σp) of the tested steels increase as the deformation temperature decreases and the strain rate increases. Additionally, a higher V content leads to an increase in σc and σp, thereby suppressing the occurrence of DRX. Compared to 0.1V steel, 0.2V steel precipitates a greater quantity of carbides at the grain boundaries (GBs), which effectively stabilizes the GBs and inhibits the growth of DRX grains. In contrast, 0.1V steel achieves DRX over a wider range of Z parameters (at lower temperatures and higher strain rates). The activation energies for hot deformation (Q) of the two tested steels are 479.100 kJ/mol and 438.274 kJ/mol, respectively. The hot processing maps indicate that an increase in V content reduces the hot workability of high-manganese steel. The optimal temperature and strain rate for hot processing of 0.1V steel are 1035–1095 °C and 0.01–0.0451 s⁻1, respectively. For 0.2V steel, the optimal hot processing parameters are a temperature of 1065–1100 °C and a strain rate of 0.01–0.07 s⁻1.